RHEA: resource hypervisor and efficient allocator in cloud - Priyatharsini, G Soniya; Malarvizhi, N (International Journal of Engineering and Technology, 2018)
In this modern world, people are not ready to waste their time in waiting for long duration. That’s why cloud computing is such an enormous number of fans that it can be rented and also pay per use. The cloud service provider is concern about the data owner’s satisfaction in cloud usage. The main area they concentrate will be the security of the owner’s data and the resource allocation as per the request. This paper explains how the resources are efficiently allocated and scheduled to the clients. It follows four steps; firstly it identifies the active PMs. Next it defragments the identified machines. Then it balances the load along with the threshold feature to enhance the usage of the resource utilization. Finally it allocates the efficient Virtual Machines (VM) to the data owner as per the request. This is done using cloudsim along with java.